Simultaneous Determination of Selegiline, Desmethylselegiline, R/S-methamphetamine, and R/S-amphetamine on Dried Urine Spots by LC/MS/MS: Application to a Pharmacokinetic Study in Urine - Chen, Lizhu; Yu, Yingjia; Duan, Gengli; Wang, Xin; Shen, Baohua; Xiang, Ping (Frontiers in Chemistry, 2019)
Objective Chiral analysis is a crucial method to differentiate selegiline intake from drug abuse. A dried urine spot (DUS) analytical method based on spotting urine samples (10 μL) onto dried spot collection cards followed by air-drying and extraction was developed and validated for the determination of selegiline, desmethylselegiline, R/S-methamphetamine, and R/S-amphetamine. Methods Methanol (0.5 mL) was found to be the ideal extraction solvent for target extraction from DUSs under orbital-horizontal stirring on a lateral shaker at 1450 rpm for 30 min. Determinations were performed by direct electrospray ionization tandem mass spectrometry (ESI-MS/MS) under positive electrospray ionization conditions using multiple reaction monitoring mode. The chromatographic system consisted of a ChirobioticTM V2 column (2.1 mm × 250 mm, 5 μm) and a mobile phase of methanol containing 0.1% (v/v) glacial acetic acid and 0.02% (v/v) ammonium hydroxide. Results and conclusions The calibration curves were linear from 50 to 5000 ng/mL, with r > 0.995 for all analytes, imprecisions ≤ 15% and accuracies between -11.4% and 11.7%. Extraction recoveries ranged from 48.6 to 105.4% with coefficients of variation (CV) ≤ 13.7%, and matrix effects ranged from 45.4 to 104.1% with CV ≤ 10.3%. The lower limit of quantification was 50 ng/mL for each analyte. The present method is simple, rapid (accomplished in 12 min), sensitive, and validated by a pharmacokinetic study in human urine collected after a single oral administration of SG.